MENGKAJI POLA ASUH OTORITER TERHADAP KELEKATAN PADA DEWASA AWAL - Wahyu Aulizalsini Alurmei; Nina Perunaziah; Widya Graha Mangkading; Dinda Ophelia; M. Al Afif Annasai (CV. ADIBA AISHA AMIRA, 2024)
Attachment is an emotional bond between children and parents that lasts long enough in the span of human life, leading children to feel pleasure when they interact with them. Authoritarian parenting is a parent's restriction of a child's actions or behavior by setting standard parental rules that the child must obey and providing punishment if the child breaks the rules, but authoritarian parents pay little attention to the child. This research aims to explain the influence of authoritarian parenting on early adulthood's attachment to parents. This research uses a quantitative approach with a simple linear regression research type. The population used in this research were active students at University X in North Bekasi. In this research, the data collection technique was by distributing questionnaires via Google Form which contained instruments from a psychological scale. To make things easier for researchers, data analysis was carried out using IBM SPSS Statistics version 25 software. Based on the results of data analysis, it shows that in this study students at University their parents' authoritarian upbringing. Then a significance value of 0.112 > 0.05 was obtained, so it can be concluded that authoritarian parenting has no effect on attachment in early adulthood.